2016
DOI: 10.1634/theoncologist.2015-0362
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Colorectal Cancer During Pregnancy: Cytotoxic Chemotherapy and Targeted Therapy Challenges

Abstract: Cancer diagnosed during pregnancy has increased because of delayed child-bearing and the known occurrence of agedependent malignancies. Cases of colorectal cancer (CRC) in pregnancy have recently been reported. With the expected rise in CRC diagnosed in young adults coupled with the current trend of delayed child-bearing, CRC during pregnancy is likely to increase. Treating pregnant women with CRC by using antineoplastics presents a dilemma because there are many unknowns to guide treatment decisions. We revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…[10][11][12][13][14][15] Overviews of the challenges of chemotherapy during pregnancy provide valuable guidance. 8,19,20 Because the patient's need for treatment contrasts with the child's challenges by being prematurely delivered, interdisciplinary cooperation is necessary, including surgeons, oncologists, and obstetricians.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12][13][14][15] Overviews of the challenges of chemotherapy during pregnancy provide valuable guidance. 8,19,20 Because the patient's need for treatment contrasts with the child's challenges by being prematurely delivered, interdisciplinary cooperation is necessary, including surgeons, oncologists, and obstetricians.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of chemotherapy for CRC discussed the different drugs in detail and reported on outcomes and safety of published case reports. 8 A monograph on the developmental effects and pregnancy outcomes associated with chemotherapy during pregnancy reports on several individual chemotherapeutics. 25 These publications, along with the case reports, were valuable for guiding the treatment decision of the reported patient, who started chemotherapy with a FOLFOX regimen toward the end of the second trimester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations